2001
DOI: 10.1104/pp.010841
|View full text |Cite
|
Sign up to set email alerts
|

Control of Outgrowth and Dormancy in Axillary Buds

Abstract: The shoot system has an important role in generating a large variety of diverse plant forms (Steeves and Sussex, 1989). The overall architecture of the shoot system is derived from the activity of the primary shoot apical meristem (SAM), arising during embryogenesis, together with the activity of the additional meristems subsequently formed after seed germination. The primary SAM provides the main axis of the plant body. Plant architecture is further modified by shoot branching that results from the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
2
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(127 citation statements)
references
References 74 publications
(72 reference statements)
1
121
2
3
Order By: Relevance
“…However, more recent studies have suggested that cytokinin synthesized locally in the node may play a role in the regulation of branching. After decapitation, a pea adenylate IPT gene was found to be upregulated in nodes from which branches would grow out (Shimizu-Sato and Mori, 2001). Therefore the increased cytokinin content of uninhibited buds could be caused by the uptake of cytokinin synthesized within the node, with auxin acting to control uptake and/or synthesis.…”
Section: Relationship Between Auxin and Cytokinin In The Regulation Omentioning
confidence: 99%
“…However, more recent studies have suggested that cytokinin synthesized locally in the node may play a role in the regulation of branching. After decapitation, a pea adenylate IPT gene was found to be upregulated in nodes from which branches would grow out (Shimizu-Sato and Mori, 2001). Therefore the increased cytokinin content of uninhibited buds could be caused by the uptake of cytokinin synthesized within the node, with auxin acting to control uptake and/or synthesis.…”
Section: Relationship Between Auxin and Cytokinin In The Regulation Omentioning
confidence: 99%
“…In Arabidopsis, dormancy occurs e.g. in axillary buds that are suppressed by apical dominance (Shimizu-Sato and Mori, 2001). Previous work has established patterns of gene expression changes in lateral buds upon release of apical dominance, and identified two expression markers that are highly expressed in dormant buds, the DORMANCY-ASSOCIATED PROTEIN1 and 2 (AtDRM1 and AtDRM2) genes (Tatematsu et al, 2005).…”
Section: Gpa Represents a Form Of Shoot Dormancymentioning
confidence: 99%
“…Also known as ''release of suppressed/axillary buds'', it comes with ageing, trauma and bending, affecting the tree growth form (e.g. Brown 1974;Shimizu-Sato and Mori 2001). It is envisaged that in a tree, active apical meristem releases auxin that inhibits the growth of lateral buds (apical dominance) so when the apex is removed (by flowering or pruning), the apical dominance stops and lateral buds awake (Brown 1974;Cline 1997)…”
Section: Modularity and The Tree Architecture Of The Dragon Treementioning
confidence: 99%